2010
DOI: 10.1002/app.32394
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of acetophenone formaldehyde resin containing ABA type block copolymers by ATRP

Abstract: Well‐defined ABA type block copolymers of acetophenone formaldehyde resin (AFR) and methyl methacrylate (MMA) were synthesized via atom transfer radical polymerization. In the first step, acetophenone formaldehyde resin containing hydroxyl groups was modified with 2‐bromopropionyl bromide. Resulting difunctional macroinitiator was used in the ATRP of MMA using copper bromide (CuBr)/N,N,N′,N″,N″‐pentamethyl‐diethylenetriamine (PMDETA) as the catalyst system at 90°C. The chemical composition and structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…[36][37][38][39] Also, the polymerization of fully phenyl fluorinated styrene, 2,3,4,5,6-pentafluorostyrene, and 2,3,5,6-tetrafluoro-4-methoxy styrene monomers has been successfully carried out via ATRP. 46 It was found that pSt and PMMA with fluorinated end groups imparted high hydrophobic characteristics to the materials, even at low fluorine contents. 44 By the inclusion of fluorinated moieties in the initiators, semifluorinated pSt and PMMA copolymers have been obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38][39] Also, the polymerization of fully phenyl fluorinated styrene, 2,3,4,5,6-pentafluorostyrene, and 2,3,5,6-tetrafluoro-4-methoxy styrene monomers has been successfully carried out via ATRP. 46 It was found that pSt and PMMA with fluorinated end groups imparted high hydrophobic characteristics to the materials, even at low fluorine contents. 44 By the inclusion of fluorinated moieties in the initiators, semifluorinated pSt and PMMA copolymers have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the synthesis of a new fluorinated initiator, 3,5 bis(perfluorobenzyloxy)benzyl 2-bromopropanoate bearing perfluorinated aromatic groups, and used this initiator to carry out the ATRP of styrene and methyl methacrylate (MMA) monomers. 46 It was found that pSt and PMMA with fluorinated end groups imparted high hydrophobic characteristics to the materials, even at low fluorine contents. The resulting chain-end fluorinated polymers exhibited higher hydrophobicity than the pure PMMA and pSt.…”
Section: Introductionmentioning
confidence: 99%